LncRNA HOTAIR promotes MPP+-induced neuronal injury in Parkinson’s disease by regulating the miR-874-5p/ATG10 axis - Zhao, Jingya; Li, Hongli; Chang, Na (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Parkinson’s disease (PD) is a neurodegenerative disease caused by the loss of dopaminergic neurons. Long non-coding RNAs (lncRNAs) play an important role in many neurological diseases, including PD. This study aimed to investigate the role of lncRNA HOX transcript antisense RNA (HOTAIR) in PD pathogenesis and its potential mechanism. SK-N-SH cells were exposed to 1-methyl-4-phenylpyridinium (MPP+) to mimic PD model in vitro. The levels of HOTAIR, miR-874-5p and autophagy-related 10 (ATG10) were determined by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot assay. Cell viability and apoptosis were assessed by Cell Counting Kit-8 (CCK-8) assay and flow cytometry. The expression of apoptosis-related proteins was measured by western blot. The levels of neuroinflammation-related factors were detected by enzyme-linked immunosorbent assay (ELISA). Commercial kits was used to monitor lactate dehydrogenase (LDH) activity, reactive oxygen (ROS) generation and superoxide dismutase (SOD) activity. The interaction among HOTAIR, miR-874-5p and ATG10 were verified by dual-luciferase reporter assay or RNA immunoprecipitation (RIP) assay. HOTAIR and ATG10 were up-regulated, and miR-874-5p was down-regulated in dose- and time-dependent manners in MPP+-treated SK-N-SH cells. HOTAIR knockdown reduced MPP+-induced neuronal damage. HOTAIR aggrandized MPP+-triggered neuronal injury by sponging miR-874-5p. Also, miR-874-5p attenuated MPP+-triggered neuronal damage by targeting ATG10. Moreover, HOTAIR regulated ATG10 expression via sponging miR-874-5p. HOTAIR promoted MPP+-induced neuronal injury via modulating the miR-874-5p/ATG10 axis in SK-N-SH cells.
EXCLI Journal;Vol. 19 2020
Keywords: Parkinson’s disease; HOTAIR; miR-874-5p; ATG10; Neuronal injury; 610